Training Programme for Professional Nurses who Care for Patients with Type 2 Diabetes - Sechabe, Ednah Virginia; Mothiba, Tebogo Maria; Bastiaens, Hilde (Africa Journal of Nursing and Midwifery, 2020)
Increasing urbanisation and rising unhealthy lifestyle risk factors are contributing to a growing diabetes epidemic worldwide. South Africa like many other countries is continually reporting an increase in the prevalence of diabetes. Education and training play an essential role in the provision of the quality of patient care. In this study, a conceptual framework based on the practice-oriented theory by Dickoff, James, and Wiedenbach was used to develop the training programme for professional nurses who care for patients with diabetes. The aim of this article was to describe a conceptual framework which guided the development of a training programme for the professional nurses who care for patients with diabetes. A mixed-method research design was used. The accessible population for this study consisted of professional nurses who care for patients with diabetes in the three Ga-Dikgale village clinics that are situated in the Limpopo province of South Africa. Purposive sampling was used. Both semi-structured and structured interviews were used to collect data for this study. Diverse levels of knowledge among professional nurses were identified where some professional nurses lack knowledge while others have knowledge related to diabetes. A lack of continuous training on care of patients with diabetes was also identified. Challenges related to patients’ socio-economic status, inadequate knowledge about diabetes, misconceptions, denial, and a lack of resources for patient care that leads to poor treatment outcomes led to a framework for a context-specific training programme. There is a need for a context-specific training programme for professional nurses who care for patients with diabetes which could improve patient care.